Analysis of strategic planning and forecasting approaches used in the transport industry of the Russian Federation - Elvira B. Trepashova (Наука Красноярья)
This article is aimed at analyzing strategic management in the development of the Russian transport system in order to form an understanding of current approaches and planning and implementation tools for the possibility of developing new approaches to improve the effectiveness of management in the industry. The relevance of the article lies in the fact that modernity is characterized by uncertainty and variability of economic processes, and the transport system plays a key role in the development of any country, especially such an extensive one as Russia.